Endoscopic tissue shielding method with polyglycolic acid sheets and fibrin glue to prevent delayed perforation after duodenal endoscopic submucosal dissection. (April 2014) - Takimoto, Kengo; Imai, Yoshihito; Matsuyama, Kiichi
Abstract : Delayed perforation after duodenal endoscopic submucosal dissection (ESD) occurs at a high rate because the duodenal wall is very thin and the artificial ulcer after resection is exposed to bile and pancreatic juice. We investigated the application of the combination of a polyglycolic acid (PGA) sheet and fibrin glue. PGA sheets comprise materials widely used in surgery for absorbable thread. Fibrin glue is a heated blood product and is used for hemostasis during operations. We developed a combined method using both materials. We have used this method in two cases. One case involved an elevated lesion located in the lower duodenal angle of the duodenum. The other involved an elevated lesion in the second portion of the duodenum. About 1 week after ESD, the PGA sheets remained covering the ulcer and delayed perforation did not occur. We were able to easily carry out this method for several parts of the duodenum. This method may be helpful for the prevention of delayed perforation after duodenal ESD.